Who sits behind the telephone?: interpersonal characteristics of volunteer counselors in telephone emergency services - Rek, Isabelle; Dinger, Ulrike (Journal of counseling psychology, 2016)
APA PsycNet DoiLanding page
Gesehen am 22.10.2021